2015
DOI: 10.1021/acs.jpcb.5b01567
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Measurements of Dielectric and Optical Functions of Liquid Water and Liquid Benzene in the VUV Region (1–100 eV) Using Small-Angle Inelastic X-ray Scattering

Abstract: Using a third-generation synchrotron source (the BL12XU beamline at SPring-8), inelastic X-ray scattering (IXS) spectra of liquid water and liquid benzene were measured at energy losses of 1-100 eV with 0.24 eV resolution for small momentum transfers (q) of 0.23 and 0.32 au with ±0.06 au uncertainty for q. For both liquids, the IXS profiles at these values of q converged well after we corrected for multiple scattering, and these results confirmed the dipole approximation for q ≤ ∼0.3 au. Several dielectric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 86 publications
3
74
1
Order By: Relevance
“…Such limitations are discussed in detail by Thomson et al 91 and Liljequist et al 92 Although it was already shown 47 that "option 4" constructor improves upon "option 2" at various track structure simulations at sub-keV energies, the latter is still used since it covers a larger energy range up to 1 MeV ("option 4" has an upper limit of 10 keV and "option 6" of 256 keV). The "option 4" constructor will soon be extended to relativistic energies, benefiting notably from newly available experimental data and theoretical calculations, 83,93 which will extend its usage to a variety of applications beyond 10 keV. These examples will then be used to quantify the impact of such extended models on TS simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Such limitations are discussed in detail by Thomson et al 91 and Liljequist et al 92 Although it was already shown 47 that "option 4" constructor improves upon "option 2" at various track structure simulations at sub-keV energies, the latter is still used since it covers a larger energy range up to 1 MeV ("option 4" has an upper limit of 10 keV and "option 6" of 256 keV). The "option 4" constructor will soon be extended to relativistic energies, benefiting notably from newly available experimental data and theoretical calculations, 83,93 which will extend its usage to a variety of applications beyond 10 keV. These examples will then be used to quantify the impact of such extended models on TS simulations.…”
Section: Resultsmentioning
confidence: 99%
“…[20,22], for the IR and visible range [26,24]. A measured UV spectrum for ice-cold water is not available, hence we assumed minimal temperature dependence across 0-25 • C in the UV and used the same room-temperature data from Hayashi [27]. This assumption can be justified since thermal energy (k B T ) at room temperature is 25.8 meV, far below UV energies (> 1 eV) reported in Ref.…”
Section: Available Data and Models For Dielectric Function Of Watermentioning
confidence: 99%
“…At photon energies higher than a few ten eV, where n < 1 [26], nanofocusing is not observable either. As a result, we find that for many substances it is not possible to realize nanofocusing with single-photon VUV excitation, neither by variation of the wavelengths nor by variation of the particle size.…”
mentioning
confidence: 93%